(untitled) (Research, Society and Development, 2020)
This study aims to analyze the scientific production related to facing accessibility barriers for people with disabilities and / or reduced mobility and the impacts on health, social inclusion and citizenship of these people. This is an integrative review carried out in the Lilacs, SCiELO, Ibecs, Bdenf and MedLine databases, including national and international publications between 2008 and 2017. 21 studies were included in the categories: Accessibility Barriers that compromise the Exercise of Citizenship, Barriers to Accessibility that Difficult Access to Health Services and Accessibility Barriers that Threaten Social Inclusion. We observed that the architectural barriers were mentioned by the study participants as the main factor for impeding their activities, with a strong impact on social inclusion. We realize that it is not a disability that makes them incapable, but the imposed barriers that limit their capabilities.